Comparative Studies of Author Identification algorithms for Telugu Classical Poems - Pandian, A.; Manikandan, K.; Ramalingam, V.; Sai Krishna, Pavuluri; Jeevan Reddy, V. (International Journal of Engineering and Technology, 2018)
Creator recognizable proof is the assignment of distinguishing the creator of a given test from an arrangement of suspects. The fundamental worry of this assignment is to characterize a fitting portrayal of test that catches the written work styles of writers. In this task, weka based machine learning apparatuses are utilized for ID of creator for include extraction of reports spoke to utilizing variable size character n-grams. We composed our own java program to extricate the highlights like number of words, sentences and so on. From, the ballad which thusly sustained as contribution to weka device for the recognizable proof of creator then in the wake of testing the contribution with all the calculation all the exactness rates are noted down to see which calculation is given us the best precision rate. Presently to discover the creator name for a mysterious sonnet the lyric highlights are extricated utilizing the java code and the yield is taken in the java record given to the weka instrument and tried with the calculations and after that the creator name is given to the unknown ballads.Â